Bloc by bloc how to build a global enterprise for the new regional order - Weber, Steve, 1961- (Harvard University Press, 2019)
Globalization is taking a step backward. What, then, is the best way to organize a global enterprise? The key, Steven Weber explains, is to prepare for a world increasingly made up of competing regions with distinct rules and standards. This new condition could be more prosperous, but there will also be more friction and therefore more risk